Aerobic glycolysis tunes YAP/TAZ transcriptional activity. (21st March 2015) - Enzo, Elena; Santinon, Giulia; Pocaterra, Arianna; Aragona, Mariaceleste; Bresolin, Silvia; Forcato, Mattia; Grifoni, Daniela; Pession, Annalisa; Zanconato, Francesca; Guzzo, Giulia; Bicciato, Silvio; Dupont, Sirio
Abstract Increased glucose metabolism and reprogramming toward aerobic glycolysis are a hallmark of cancer cells, meeting their metabolic needs for sustained cell proliferation. Metabolic reprogramming is usually considered as a downstream consequence of tumor development and oncogene activation; growing evidence indicates, however, that metabolism on its turn can support oncogenic signaling to foster tumor malignancy. Here, we explored how glucose metabolism regulates gene transcription and found an unexpected link with YAP/TAZ, key transcription factors regulating organ growth, tumor cell proliferation and aggressiveness. When cells actively incorporate glucose and route it through glycolysis, YAP/TAZ are fully active; when glucose metabolism is blocked, or glycolysis is reduced, YAP/TAZ transcriptional activity is decreased. Accordingly, glycolysis is required to sustain YAP/TAZ pro‐tumorigenic functions, and YAP/TAZ are required for the full deployment of glucose growth‐promoting activity. Mechanistically we found that phosphofructokinase (PFK1), the enzyme regulating the first committed step of glycolysis, binds the YAP/TAZ transcriptional cofactors TEADs and promotes their functional and biochemical cooperation with YAP/TAZ. Strikingly, this regulation is conserved in Drosophila, where phosphofructokinase is required for tissue overgrowth promoted by Yki, the fly homologue of YAP. Moreover, gene expression regulated by glucose metabolism in breast cancer cells is strongly associated in a large dataset of primary human mammary tumors with YAP/TAZ activation and with the progression toward more advanced and malignant stages. These findings suggest that aerobic glycolysis endows cancer cells with particular metabolic properties and at the same time sustains transcription factors with potent pro‐tumorigenic activities such as YAP/TAZ.